Three dimensional analysis of the retinal vasculature using immunofluorescent staining and confocal laser scanning microscopy. Issue 3 (March 1996) - Foreman, D M; Bagley, S; Moore, J; Ireland, G W; McLeod, D; Boulton, M E
Abstract : AIM: To undertake a qualitative and quantitative analysis in three dimensions of the human retinal vasculature. METHOD: Fixed and excised whole retinas were permeabilised and subjected to immunofluorescent staining for blood vessel components followed by confocal laser scanning microscopy. Single projection and stereoimages were constructed using computer software. XZ sections through the retina were constructed and the vasculature analysed using appropriate software. RESULTS: Immunofluorescent staining with no discontinuities was present in vessels of all sizes, the confocal images of the capillary network being free of out of focus blur at all depths. Quantitative analysis of XZ sections confirmed the qualitative impression of sharp delineation of the deep retinal capillary plexus, an absence of laminar arrangement of capillaries within the inner retina, and a truncated cone of capillaries around the foveal avascular zone (FAZ) wherein the superficial capillaries approached the FAZ more closely than those in the deeper retina. CONCLUSION: Immunofluorescent staining of the retina and confocal laser scanning microscopy were shown to be useful in analysing accurate three dimensional reconstructions of the normal retinal vasculature without affecting overall tissue architecture.